Intermittent use of an anchor system improves postural control in healthy older adults - Freitas, Milena de Bem Zavanella; Mauerberg-deCastro, Eliane [UNESP]; Moraes, Renato (Elsevier, 2013)
Haptic information, provided by a non-rigid tool (i.e., an anchor system), can reduce body sway in individuals who perform a standing postural task. However, it was not known whether or not continuous use of the anchor system would improve postural control after its removal. Additionally, it was unclear as to whether or not frequency of use of the anchor system is related to improved control in older adults. The present study evaluated the effect of the prolonged use of the anchor system on postural control in healthy older individuals, at different frequencies of use, while they performed a postural control task (semi-tandem position). Participants were divided into three groups according to the frequency of the anchor system's use (0%, 50%, and 100%). Pre-practice phase (without anchor) was followed by a practice phase (they used the anchor system at the predefined frequency), and a post-practice phase (immediate and late-without anchor). All three groups showed a persistent effect 15. min after the end of the practice phase (immediate post-practice phase). However, only the 50% group showed a persistent effect in the late post-practice phase (24. h after finishing the practice phase). Older adults can improve their postural control by practicing the standing postural task, and use of the anchor system limited to half of their practice time can provide additional improvement in their postural control. © 2013 Elsevier B.V.
Keywords: Anchor system; Haptic information; Older adults; Postural control; adult; aged; anchor system; body equilibrium; body posture; cognition; female; general device; human; human experiment; male; motor control; normal human; postural control; priority journal; standing; task performance